The Effect of Green Investment, Good Corporate Governance on Company Values From an Islamic Economic Perspective - Nursella, Ike; Putri, Rosydalina; Nurhayati, Nurhayati (LifeSciFi, 2025)
This research aims to analyze the influence of green investment, institutional ownership, and managerial ownership on the value of companies in the energy sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. The research method used is an associative quantitative approach with panel data obtained from annual reports and corporate sustainability reports. The sampling technique used purposive sampling with a total of 15 companies over six years of observation. Data analysis was performed using panel data regression with the Random Effect Model (REM) approach through Eviews 12 software, after undergoing Chow, Hausman, and Lagrange Multiplier tests. The results show that green investment and institutional ownership have a significant positive effect on company value, while managerial ownership has no significant effect. This confirms that green investment practices and institutional oversight contribute to increasing the value and sustainability of energy sector companies in Indonesia.